COMO UTILIZAR A PESQUISA PARA MELHOR ORIENTAR A AÇÃO DA ENFERMAGEM - Amália C. de Carvalho
The author showed the importance of the utilization of scientific methodology in nursing, giving emphasis on the need of employing it in the solution of nursing problems met both in nursing education and nursing practice. She stressed the need of offering the nurses opportunities to improve the knowledge in their own specialties and in the research methodology.